How peritoneal dialysis transforms the peritoneum and vasculature in children with chronic kidney disease-what can we learn for future treatment? - Maria Bartosova; Sotirios G. Zarogiannis; Claus Peter Schmitt; for the Members of the International Pediatric Peritoneal Biobank (SpringerOpen, 2022)
Abstract Children with chronic kidney disease (CKD) suffer from inflammation and reactive metabolite-induced stress, which massively accelerates tissue and vascular aging. Peritoneal dialysis (PD) is the preferred dialysis mode in children, but currently used PD fluids contain far supraphysiological glucose concentrations for fluid and toxin removal and glucose degradation products (GDP). While the peritoneal membrane of children with CKD G5 exhibits only minor alterations, PD fluids trigger numerous molecular cascades resulting in major peritoneal membrane inflammation, hypervascularization, and fibrosis, with distinct molecular and morphological patterns depending on the GDP content of the PD fluid used. PD further aggravates systemic vascular disease. The systemic vascular aging process is particularly pronounced when PD fluids with high GDP concentrations are used. GDP induce endothelial junction disintegration, apoptosis, fibrosis, and intima thickening. This review gives an overview on the molecular mechanisms of peritoneal and vascular transformation and strategies to improve peritoneal and vascular health in patients on PD.